Introduction to chemical engineering thermodynamics - Smith, J. M.; Ness, Hendrick C Van.; Abbott, Michael; Ness, Hendrick Van. ([S.l.] : McGraw-Hill Science/Engineering/Math, 2000)
Introduction to Chemical Engineering Thermodynamics, 6/e, presents comprehensive coverage of the subject of thermodynamics from a chemical engineering viewpoint. The text provides a thorough exposition of the principles of thermodynamics and details their application to chemical processes. The chapters are written in a clear, logically organized manner, and contain an abundance of realistic problems, examples, and illustrations to help students understand complex concepts. New ideas, terms, and symbols constantly challenge the readers to think and encourage them to apply this fundamental body of knowledge to the solution of practical problems. The comprehensive nature of this book makes it a useful reference both in graduate courses and for professional practice. The sixth edition continues to be an excellent tool for teaching the subject of chemical engineering thermodynamics to undergraduate students.
Keywords: chemical engineering,thermodynamics